Anticipation, abduction and the economy of research: The normative stance. (January 2020) - Chiffi, Daniele; Pietarinen, Ahti-Veikko; Proover, Marika
Highlights: Anticipation operates under abductive modes of reasoning. Abduction alone would explain anticipation only partially. Anticipation appeals also to principles of the economy of research . Anticipatory abduction is normative. Abstract: Anticipation operates under abductive modes of reasoning. Anticipatory abduction is normative and appeals to principles of the economy of research . As a defeasible mode of reasoning, abduction copes with fundamental uncertainty of the future in rational, logical and anticipatory manners. Abduction arises from the mind's ability to perceive logical and counterfactual relationships. This perceptual experience (i) happens on an interval, (ii) is linked to the past and (iii) is proactively and continually future-oriented. Since anticipation refers not only to reasoning about future but also to exploiting future in our present action, abduction alone would only partially explain anticipation. For this reason, we integrate it with normative facets that derive from the theory of the economy of research and the pragmatistic interpretation of abduction, as a relation between a hope that hypotheses materialize in a certain way and our decisions to act upon those hypotheses. This proposed unification of abduction, economy of research and pragmatism provides a complete Peircean methodology that can recover anticipation from its logical and pragmatistic roots.